Insights into the evolution and regulation of miRNAs from the view of their DNA replication temporal domains - Wu, Xudong; Liu, Tingting (Frontiers in Genetics, 2025)
IntroductionThe DNA replication of eukaryotes proceeds in a defined temporal sequence known as the replication timing (RT) program. A recent study revealed that the early- and late-replication temporal domains have different DNA mutation patterns and that the late-replicating sequences have a substitution pattern biased towards A and T. It raises the interesting question of how the miRNAs in the late-replication domain cope with the mutation bias caused by RT.MethodsIn this study, we characterized the genomic distribution of pre-miRNAs in relation to DNA replication timing, and identified 362 pre-miRNAs within late-replicating domains (late-miRNAs) and 631 pre-miRNAs within early-replicating domains (early-miRNAs). We comprehensively examined the multiple molecular features including the secondary structural properties, the genomic sequences surrounding the pre-miRNA loci, the Dicer processing motifs, and CAGE tag-based promoters and miRNAs expression profiles. Furthermore, we performed the simulation of miRNA-target regulatory networks to elucidate the co-regulation patterns among late-miRNAs. To advance predictive capabilities, we developed a a support vector machine (SVM) classifier based on RNA-FM embedding, enabling prediction of miRNAs’ replication timing domains.Results and DiscussionOur study indicated that the late pre-miRNAs maintained their ability to fold into hairpin structures through extending their lengths at both ends under the premise of maintaining a certain GC content of the precursors. The simulation demonstrated that the late-miRNAs tend to synergistically regulate the same genes and are involved in small molecule metabolism, immune responses and so on. The comparative analysis of early- and late- miRNAs confirmed that the information of replication timing domains is inherently encoded in miRNAs’ sequence-structure signatures, and suggested that late-replication specific mutation patterns leave direct imprints on miRNA architecture. This study provides insights into the impact of DNA replication timing on miRNA-mediated posttranscriptional regulation and helps us understand the evolutionary mechanism of miRNAs.